Justice, constructivism, and the egalitarian ethos - Kurtulmus, A; Ahmet Faik Kurtulmus (2010)
This thesis defends John Rawls’s constructivist theory of justice against three distinct challenges. Part one addresses G. A. Cohen’s claim that Rawls’s constructivism is committed to a mistaken thesis about the relationship between facts and principles. It argues that Rawls’s constructivist procedure embodies substantial moral commitments, and offers an intra-normative reduction rather than a metaethical account. Rawls’s claims about the role of facts in moral theorizing in A Theory of Justice should be interpreted as suggesting that some of our moral beliefs, which we are inclined to hold without reference to facts, are, in fact, true, because certain facts obtain. This thesis and the acknowledgement of the moral assumptions of Rawls’s constructivism help to show that Rawls does not, and does not need to, deny Cohen’s thesis. Part two defends the characterization of the decision problem in Rawls’s original position as a decision problem under uncertainty. Rawls stipulates that the denizens of the original position lack information that they could use to arrive at estimates of the likelihood of ending up in any given social position. It has been argued that Rawls does not have good grounds for this stipulation. I argue that given the nature of the value function we should attribute to the denizens of the original position and our cognitive limitations, which also apply to the denizens of the original position, their decision problem can be characterized as one under uncertainty even if we stipulate that they know that they have an equal chance of being in any individual’s place. Part three assesses the claim that a true commitment to Rawls’s difference principle requires a further commitment to an egalitarian ethos. This egalitarian ethos is offered as a means to bring about equality and Pareto-optimality. Accordingly, I try to undermine the case for an egalitarian ethos by challenging the desirability of the ends it is supposed to further or by showing that it is redundant. I argue that if primary goods are the metric of justice, then Pareto optimality in the space of the metric of justice is undesirable. I then argue that if the metric of justice is welfare, depending on the theory of welfare we adopt, an egalitarian ethos will either be redundant or will have objectionably paternalistic consequences.